Alterations in dual-task walking persist two months after mild traumatic brain injury in young adults. (September 2019) - Gagné, Marie-Ève; McFadyen, Bradford J; Cossette, Isabelle; Fait, Philippe; Gagnon, Isabelle; Sirois, Katia; Blanchet, Sophie; Le Sage, Natalie; Ouellet, Marie-Christine
Objectives: To compare dual-task performance involving different cognitive-locomotor combinations between healthy controls and participants with sub-acute mild traumatic brain injury (mTBI) and to correlate dual-task performances to history of prior head injuries. Methods: Eighteen participants having recently sustained mTBI and 15 controls performed nine dual-tasks combining locomotor (level-walking, narrow obstacle, deep obstacle) and cognitive (Stroop task, Verbal fluency, Counting backwards) tasks. Previous history of concussion was also investigated. Results: Slower gait speeds were observed in the mTBI group compared to controls during both single and dual-tasks. Longer response times to cognitive tasks in the mTBI group further suggested the presence of residual impairments two months following injury. No combination of dual-task was more sensitive. Correlations were observed between history of mTBI and several measures of dual-task performance, underlying the need to further consider the effects of multiple injuries in relation to dual-task walking. Conclusion: Dual-tasks using simultaneously locomotor and cognitive functions represent an ecological way for clinicians to detect residual, but subtle, alterations post-mTBI. History of previous mTBI needs to be considered as a personal characteristic which may influence dual-task walking performance.